Pathogenic microbe detection in placental tissues supports placental pathobiome association with preterm birth risk in Pakistani women: A brief snapshot. (August 2022) - Saraf, Viqar Sayeed; Ali Zaidi, Syed Shujaat; Zhu, Jay; Gillevet, Patrick; Sikaroodi, Masoumeh; Bokhari, Habib; Javed, Sundus
Abstract: Preterm birth (PTB) poses great risk to neonatal health in Pakistan with few tertiary health care facilities. Role of intrauterine microbiome in maintaining healthy pregnancy has been highlighted. However, there is ongoing debate whether a true placental microbiome exist. We analyzed placental and vaginal microbiome through V3–V4 16srRNA sequencing and observed increased abundance of proteobacteria, with concomitant decline in the firmicutes population in preterm vagina. Simplistic placental microflora included many environmental microbes with PTB placenta carrying pathogenic microbes like ureaplasma and mycoplasma species . We observed contribution of environmental, vaginal and skin contamination in term versus pathobiome signatures in preterm placenta. Highlights: Placental and vaginal microbiome analysis with control differentiate among contamination and tissue associated signatures. Preterm vagina depicts increased abundance of proteobacteria, acetinobacter and tenericutes, with decline in firmicutes. Placenta shows simplistic microflora with environmental and vaginal contamination in term and preterm tissue. Pathogenic microbes in preterm placenta only provide probable evidence of role of pathobiome in preterm birth.